Families in motion : ebbing and flowing through space and time - Murray, Lesley; McDonnell, Liz; Hinton-Smith, Tamsin; Ferreira, Nuno; Walsh, Katie (Emerald Publishing Limited, 2019)
This interdisciplinary edited collection will challenge the idea of the static family that can be 'broken', and instead think of family as always 'on the move', both conceptually and in practice. This dual approach to family is the unique contribution of the book, which offers new perspectives on the sociology and geography of the family, drawn together by the shared lens of family mobilities. As such it brings together insights from the diverse work of interdisciplinary academics working alone and collaboratively on different aspects of family lives and relationships. The central argument of the book is that the concept of family is always in motion: a disruption in one aspect of family relations, for example, the ending of the intimate relationship between parents, is part of the ongoing project of family. In addition, families are made through mobility and immobility in relation to people, communications, objects and ideas. Contributions from a range of academics across disciplines consider changes in family practices and the ways in which they are produced through motion. This book seeks to understand families as always in motion; changing, adapting and re-routed. Integral to this discussion is the spatiality and temporality of family, that families are produced in different times and spaces. Families are also made through interactions with material things, including non-human living things and through the emotional ties and responses that determine their form and practices.